The role of microglia in multiple sclerosis: implications for treatment with Bruton’s tyrosine kinase inhibitors - Vermersch, Patrick; Airas, Laura; Berger, Thomas; Deisenhammer, Florian; Grigoriadis, Nikolaos; Hartung, Hans-Peter; Magyari, Melinda; Popescu, Veronica; Pozzilli, Carlo; Pugliatti, Maura; Van Wijmeersch, Bart; Zakaria, Magd; et al. (Frontiers in Immunology, 2025)
BackgroundMultiple sclerosis (MS) is a chronic autoimmune disease affecting the central nervous system (CNS), characterized by inflammation and neurodegeneration. The pathophysiology of MS, especially its progressive forms, involves various cellular components, including microglia, the primary resident immune cells of the CNS. This review discusses the role of microglia in neuroinflammation, tissue repair, and neural homeostasis, as well as their involvement in MS and explores potential therapeutic strategies targeting microglial function.MethodsA literature search conducted in August 2023 and updated in March 2025, using the PubMed database, focused on articles relating to microglia and MS published in 2018–2025. Additionally, ongoing clinical trials of Bruton’s tyrosine kinase (BTK) inhibitors were identified through the ClinicalTrials.gov website in November 2023 and updated in March 2025.ResultsMicroglia are highly adaptive and exhibit various functional states throughout different life stages and play critical roles in neuroinflammation, tissue repair, and neural homeostasis. Their altered activity is a prominent feature of MS, contributing to its pathogenesis. Imaging techniques such as magnetic resonance imaging (MRI) and positron emission tomography (PET) provide insights into microglial activity in MS. BTK inhibitors and other novel treatments for MS, including masitinib and frexalimab, show promise in modulating microglial function and influencing the disease progression rate.ConclusionsThe multifaceted roles of microglia in CNS development, immune surveillance, and particularly in the pathogenesis of MS highlight the potential of targeting microglial functions in MS treatment. Emerging research on the involvement of microglia in MS pathophysiology offers promising avenues for developing novel therapies, especially for progressive MS, potentially improving patient outcomes in this debilitating disease.